Two organic–inorganic hybrids constructed from metal/ttb segments and different polyoxometalates: Syntheses, structures and multifunctional catalytic properties. (15th February 2018) - Wang, Xiang; Lin, Lin; Yu, Xiaowen; Liu, Jiahuan; Lin, Hongyan; Liu, Guocheng
Graphical abstract: Two organic–inorganic hybrids composed of metal/ttb segments and different polyoxoanions have been synthesized, not only indicating the influences on the final structures of polyoxoanions, but also displaying multifunctional catalytic properties. Abstract: Two organic–inorganic hybrids self-assembled from metal/ttb segments and polyoxometalates, [Co2 (ttb)2 (H2 O)4 (H2 P2 W18 O62 )]·10H2 O (1 ) and [Cu2 (ttb)2 (H2 O)4 ](SiW12 O40 ) (2 ) [ttb = 1, 3, 5-tris(triazol-1-ylmethyl)-2, 4, 6-trimethyl benzene], have been synthesized hydrothermally. Both1 and2 have 3D supramolecular structures, where the combination of the ttb ligands and metal centers gives two kinds of metal–organic segments, namely, a 1D metal–organic belt [Cu2 (ttb)2 (H2 O)4 ] n 4 n + in1, a 2D cationic layer [Cu2 (ttb)2 (H2 O)4 ] n 4 n + in2 . Interestingly, compound1 displays multifunctional catalytic properties, including not only the electrocatalytic reduction for hydrogen peroxide, but also the electrocatalytic oxidation for ascorbic acid, as well as the photocatalytic degradation of MB under UV irradiation.